PEMAKAIAN MEDICAL RAPID PROTOTYPING UNTUK PREKONTUR PLAT REKONSTRUKSI PADA RESEKSI MANDIBULA - Arya Kusuma Agraha; Masykur Rahmat; Rahardjo . (ODONTO : Dental Journal, 2017)
Background: In the case of mandibular resection that leaves a large mandibular bone defect, a mandibular reconstruction is required to restore functional and postoperative aesthetic factors. Mandibular reconstruction plate installation on mandibular resection is very important but difcult to achieve maximum results. The formation of reconstruction plates can be preoperative and intraoperative. Preoperative stereolithography (medical rapid prototyping/MRP) can be used to form rapid and accurate plates (precontours). Objective: Report the use of MRP as an alternative tool to precontour mandibular reconstruction plate.Case management: Reported reconstruction of mandibular defects in one case of hemimandibulectomy and two cases of segmental resection with avascular iliac bone grafts using MRP through a computer-aided design and computer aided manufacture procedure (CAD/CAM) to establish preoperative reconstruction plates (precontour) so the surgery doesn’t take long time to reconstruct, by forming a mandibular models under normal circumstances.Result: The formation of a reconstruction plates (precontour) using MRP (medical rapid prototyping) with CAD / CAM procedure gives results in accordance with the original form.Conclusions: The making of MRP through CAD / CAM procedure gives maximal result resembling the form of mandibular model. The MRP models get an accurate picture of the patient’s jaw as a pre contour tools for reconstruction plate. The formation of the reconstruction plates (precontour) with these MRP model is obtained from CAD / CAM and provides a normal jaw image, so that preoperative precontouring will give good and maximum result on the reconstruction plates made under the MRP models.